Insight into morphological, physicochemical and spectroscopic properties of β-chitin nanocrystalline structures. (1st December 2021) - Facchinatto, William Marcondes; dos Santos, Danilo Martins; de Lacerda Bukzem, Andrea; Moraes, Tiago Bueno; Habitzreuter, Filipe; de Azevedo, Eduardo Ribeiro; Colnago, Luiz Alberto; Campana-Filho, Sérgio Paulo
Abstract: We systematically investigated the effect of β-chitin (BCH) particle size on the preparation of nanocrystals/nanowhiskers (CWH) by acid hydrolysis. Regardless this variable, CWH aqueous suspension exhibited outstanding stability and the average degree of acetylation remained nearly constant after the acid treatment. In contrast, the morphology, dimensions, crystallinity, and molecular weight of CHW were significantly affect by the particle size. Although needle-like crystals have predominated, BCH particles sizes significantly affected the dimensions and asymmetry of CWH, as confirmed by the rheological and NMR relaxation ( T 2 ) behaviors. According to different SSNMR approaches, the acid hydrolysis meaningless affected the local chain conformation, while the spatial freedom of BCH intersheets, rated upon the mobility of methyl segments, was taken as evidence of higher permeability of acid into small particle sizes. Thus, this study demonstrated the importance of standardizing the surface/bulk proportions of β-chitin aiming to predict and control the CWH morphology and related properties.